1982
DOI: 10.1002/kin.550141003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of chamber‐dependent radical sources

Abstract: While environmental chamber data have been widely used to generate and validate computer models of the chemistry occurring in polluted atmospheres, the effects of the chambers on the gas-phase chemistry being studied have been poorly characterized. In order to investigate such chamber effects, a series of NO,-air irradiations, with trace levels of organics present to monitor OH radical concentrations, have been carried out in four different environmental chambers (ranging in volume from -100 to 40,000 L) at va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
94
2
1

Year Published

1982
1982
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(109 citation statements)
references
References 25 publications
(42 reference statements)
10
94
2
1
Order By: Relevance
“…In particular, in a series of environmental chamber experiments designed to measure OH radical levels in NOx·air irradiations, we observed an initial, rapidly-decaying radical source [6,7]. This was almost certainly due to the photolysis of initially present HONO, since direct in situ spectroscopic measurements of HOND using the DOAS technique agreed well with values calculated to fit the observed OH radical concentration-time profiles [7].…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations
“…In particular, in a series of environmental chamber experiments designed to measure OH radical levels in NOx·air irradiations, we observed an initial, rapidly-decaying radical source [6,7]. This was almost certainly due to the photolysis of initially present HONO, since direct in situ spectroscopic measurements of HOND using the DOAS technique agreed well with values calculated to fit the observed OH radical concentration-time profiles [7].…”
Section: Introductionsupporting
confidence: 59%
“…However, the amount of HONO formed prior to irradiation in our 5800-L evacuable chamber appeared to increase with the N0 2 concentration, the relative humidity and the temperature, but be independent of (or indeed decrease with) the initial NO concentration [7]. These observations showed that the heterogeneous reaction (3) wall NO + N0 2 + H20~2 HONO could not be responsible for this observed formation of HONO under these conditions, but suggested that a reaction of N0 2 with water was occurring [7].…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…9,[12][13][14] This hydrolysis reaction merits computational studies for several reasons. First, nitrous acid Figure 1.…”
Section: Introductionmentioning
confidence: 99%